2014
DOI: 10.1002/2013jb010448
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐ and strain‐dependent brittle deformation of rocks

Abstract: Key Points:• Deformation by brittle creep requires less energy than by imposed strain rate • An empirical relation between creep rate and energy deficit is exhibited • A relation between our empirical law and stress corrosion laws is determined Abstract We develop a unifying framework to quantify rate-dependent deformation in the brittle field and establish links between the microscale time-dependent crack growth processes and the macroscopically observed rate dependency. Triaxial deformation experiments have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 79 publications
(166 reference statements)
7
86
3
Order By: Relevance
“…3 Triaxial test results (confining pressure 30MPa) at constant amplitude on sandstone specimens (20-320 kN, f = 1 Hz), failure after 629 cycles, from Liu and He (2012) of rock sample strengths, producing very different results. Interestingly, such relation is also observed for cyclically loaded sands (Alarcon-Guzman et al 1989) or creep as reported later (Brantut et al 2014).…”
Section: Stress-strain Curvessupporting
confidence: 76%
See 4 more Smart Citations
“…3 Triaxial test results (confining pressure 30MPa) at constant amplitude on sandstone specimens (20-320 kN, f = 1 Hz), failure after 629 cycles, from Liu and He (2012) of rock sample strengths, producing very different results. Interestingly, such relation is also observed for cyclically loaded sands (Alarcon-Guzman et al 1989) or creep as reported later (Brantut et al 2014).…”
Section: Stress-strain Curvessupporting
confidence: 76%
“…Measurement of wave velocity is one of the most common (Rao and Ramana 1992;Lockner 1993;Meglis et al 1995;Brantut et al 2014;Voznesenskii et al 2017). Microscopic thin sections are also often provided (Ghamgosar and Erarslan 2016;Wang et al 2017).…”
Section: Crack Development and Measurementmentioning
confidence: 99%
See 3 more Smart Citations